External Counterpulsation Attenuates Hypertensive Vascular Injury Through Enhancing the Function of Endothelial Progenitor Cells - Liang, Jianwen; Shi, Jian; Wei, Wenbin; Wu, Guifu (Frontiers in Physiology, 2021)
Background Vascular injury is a landmark of hypertension and enhanced external counterpulsation (EECP) has been identified as a non-invasive treatment to restore the capacity of endothelial cells. However, the effect of EECP on blood pressure lowering in hypertension and the potential mechanism remain unknown. Methods We measured the ambulatory blood pressure（AMBP） and flow-mediated endothelial dilation (FMD) in the essential hypertensive patients who were randomly assigned to EECP group (n=20) or control group (n=20). We also evaluated in vitro function of endothelial progenitor cells (EPCs). Furthermore, multivariate analysis was performed to determine the actual correlation between EPC function and FMD. Results Compared with the control, EECP group exhibited decreased systolic [(133.2±4.9) mmHg vs. (139.3±6.4) mmHg, P<0.05] and diastolic [(83.4±4.5) mmHg vs. (89.5±7.6) mmHg, P<0.05] blood pressure and increased FMD value[(8.87±2.46) % vs. (7.51±2.32)%, P<0.01]. In addition, the migration [(47.3±6.4) /hpf vs. (33.4±5.1) hpf, P<0.05] and adhesion [(45.1±5.5) /hpf vs. (28.4±3.9) hpf, P<0.05] function of EPCs in EECP group were improved significantly, while no change was observed in the control. Both migration (OR=0.47, 95% CI: 0.27-0.64, P<0.05) and adhesion (OR=0.44, 95% CI: -0.0034-0.0012, P<0.05) of EPCs correlated with FMD. After multivariate analysis, the migration (β=3.37, 95% CI: 1.67-5.33, P<0.05) and adhesion (β=3.98, 95% CI: 1.12-6.43, P<0.05) function still independently correlated to FMD. Conclusions The present study demonstrates for the first time that EECP decreases both systolic and diastolic blood pressure and increases FMD value in hypertension. The fall in endogenous EPCs repair capacity might be an important mechanism of hypertensive vascular injury and could be restored by EECP.